The impact of different fertilization methods on some microbiological soil characteristics - Tállai, Magdolna; Sándor, Zsolt; Vágó, Imre (Acta Agraria Debreceniensis, 2008)
In our experiment, we studied the impact of an organic fertilizer, Bactofil® A10 (half- and full dosage applied in field practice) and an artificial fertilizer of Ca(NO3)2 content in different dosages (20-40 mg kg-1) – in addition to control treatments – on two different soils (calcareous chernozem, humus sandy soil) in 2005-2006, the experiment was complemented with treatments applying 250% dosage (100 mg kg-1 N, Bactofil® A10 2.5 times the field dosage) and a compost from urban sewage (25 g kg-1 compost) was also tested on these two soil types. In theexperiment, several soil microbial parameters were studied. The experiment was set up at the Department of Agrochemistry and Soil Science using 1-kg pots.Our laboratory experiments were performed at the soil microbiology laboratory of UD CAS Department of Agrochemistry and Soil Science, the total number of bacteria, microscopic fungi, nitrifying and aerob cellulose-decomposing bacteria were determined together with the CO2-production of soil, N content of the biomass and urease enzyme activity.Statistical analysis of the data was done using the program SPSS 13.0, means of the measurements, deviation and significance values were calculated. In 2005-2006, the effect of the different dosages of Bactofil® A10, and the Ca(NO3)2 fertilizer on the examined microbial parameters of calcareous chernozem and humus sandy soils can be summarized as follows:• Concerning the total number of bacteria, both treatments were effective on calcareous chernozem soil, the higher (significant) increment in bacteria number was observed in the artificial fertilizer treatments, while in the humus sandy soil Bactofil treatments had a beneficial effect. The number of microscopic fungi also increased in both treatments, higher numbers were observed in the average of two years in the Bactofil treatments.• The number of nitrifying bacteria was 2.5 times higher in both high-dosage treatments on calcareous chernozem soil, while on humus sandy soil a slight (not significant) increment was observed only int he high-dosage Bactofil treatment. The amount of aerob cellulose-decomposing bacteria significantly increased on calcareous chernozem soil in both the highdosage artificial fertilizer and the small-dosage Bactofil treatment, however, on humus sandy soil no significant increase was observed in either treatment.• The CO2-production increased in both soil types, although it was not significant in either treatment. A higher (though not significant) soil respiration was observed in the Bactofil treatments in both soil types.• The microbial biomass N values were significantly higher in the high-dosage Bactofil treatments, however, the high-dosage artificial fertilizer treatment also increased these values significantly on calcareous chernozem soil.• On calcareous chernozem soil, urease activity was significantly increased and reduced by high-dosage artificial fertilizer treatments and Bactofil treatments, respectively. On humus sandy soil, urease activity was also reduced except for the high-dosage artificial fertilizer treatment. In 2007, the pot experiment with 250% dosages was complemented with the application of compost rich in organic matter, the results of these treatments are sumnmarized as follows:• In the case of the total number of bacteria, all three treatments resulted in a significant increase on calcareous chernozem soil with the highest values in the Bactofil treatment. The Bactofil treatment was the most effective on the humus sandy soil, but the artificial fertilizer treatment alsoresulted in a significant increment. In the case of the total number of fungi, Bactofil treatments resulted in the highest values on both soils, but the compost treatment also increased the number of fungi in calcareous chernozem significantly. • The number of nitrifying bacteria was increased most (significantly) by the Bactofil and compost treatments on both soil types. The amount of cellulose-decomposing bacteria was significantly increased by he compost treatment on calcareous chernozem soil, while its effect was not significant on humus sandy soil. The number of these bacteria was increased significantly by the Bactofil treatment on humus sandy soil.• On calcareous chernozem soil, all three treatments significantly increased CO2-production, while the compost treatments had the resulted in the largest increment in soil respiration on both soil types.• The soil biomass N content was significantly increased in both soils by the compost treatment, while in the case of the humus sandy soil, the Bactofil treatment also resulted in a significant increment.• Urease enzyme activity was significantly increased by the artificial fertilizer treatment on both soils. In calcareous chernozem soil, the Bactofil treatment resulted in a slight (not significant) reduction in enzyme activity. In humus sandy soil, the Bactoful treatment also resulted in a slight reduction, while the compost treatment increased (though not significantly) the urease activity.Based on our results, it can be stated that all three treatments were effective with respect to the studied soil microbial parameters. For both the calcareous chernozem and the humus sandy soil, the organic fertilizer Bactofil and the compost with high organic matter content had a stronger effect on some soil microbial parameters than the artificial fertilizer.